A Proposal for the Use of Failure Mode and Effect Analysis as Risk Management Tool in Construction - Albasyouni, Wahbi (AUC Knowledge Fountain, 2021)
The construction sector plays a significant role in developing and improving the economy of any country and aims to keep on evolving every year. The number and magnitude of projects are increasing annually, which requires more advancements in the methods of project management to ensure completion of projects on time and according to the agreed schedule. Risk management is one of the most important aspects in managing successful construction projects worldwide. Despite that, most construction projects still suffer from cost overruns, delays in schedule of work, and poor quality. The most common form of risk management that is used is the one proposed by the Project Management Institution (PMI) where the risks are quantified through estimating their impact and probabilities. On the other hand, one of the most common risk assessment methods in the manufacturing and process design industries is the Failure Mode Effect Analysis (FMEA) which has similarities to PMI’s risk assessment with the addition of a third factor known as “detection” to help in ranking risks while considering the ability to identify them easily before they have any impact on the project. FMEA was initially used in the manufacturing industry and was considered an effective approach in the analysis of potential failure mode for machines and equipment. However, the number of studies that investigated the use of FMEA in the construction sector is limited even though that it envisaged to have substantial potential in construction projects. The goal of this research is to improve the analysis of risks in construction projects through proposing the use of FMEA. Another secondary goal is to determine the level of alignment between consultants and contractors in terms of their perception of construction risks in Egypt. To achieve these goal, the following methodology was followed. First, an extensive literature review was conducted to identify the relevant risks in the Egyptian construction industry. Second, a questionnaire survey was carried out to determine the impact, probability, and detection of the identified risk factors according to experts working in the construction sector in Egypt. Third, an analysis of these risks was carried out using traditional PMI’s risk assessment, FMEA, and fuzzy logic. Finally, alignment and lack of alignment between project parties regarding the identified risks was identified through statistical tests. The reached results demonstrated that FMEA and risk management are quite similar in different aspects, but FMEA has an additional dimension to PMI’s risk analysis, which is “detection”. Such dimension affects how we look at risks and results in changing risks ranking. This added depth provides more insights about the project risks and enables project parties to make better preparations and decisions in their projects. The research also demonstrated that there are no significant differences between project parties in their view of the probability, impact, and detection of risks, except for few of them. In addition, the findings indicate that FMEA has a significant potential in the construction industry if it is properly applied. Findings of this research are envisaged to promote the application of FMEA as an upgrade to the currently applied PMI’s risk management practice; thus enhancing the efficiency, visualization, and eventually the decision making.